TWO APPROACHES IN STUDENT ACHIEVEMENTS ASSESSMENT – PRO ET CONTRA - Nagle, Erika; Strode, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Student achievement depends very much on reliable and valid assessment methods. In this paper assessment of reflecting writing and computer based on - line tests will be discussed. The main challenge in evaluation reflecting writing tests is objectivity. For this purpose test papers were evaluated mutually by different lecturers and grading compared by Pearson`s correlation coefficient. Results showed that strong correlation exists in all compared assessor pairs. In computer based on-line test in Moodle platform evaluation is done by computer programme and grading is announced just after student finishes the test. In purpose to maintain student`s reflective skills clinical case and/or problem were included in computer based tests. These questions were evaluated manually. Two types of assessment – manual and computer based have their advantages and disadvantages. Our conclusion is that different tests and assessment methods should be used for comprehensive and objective evaluation of student`s outcomes.